Observatorio de participación para la vigilancia y protección de derechos - Cifuentes, Danny G. (2017)
Considering the methodological phases of the Observatory project, on May 15 of the year 2018, together with the beginning of the semester, he developed the first four training activities with the students assigned to this project; These workshops corresponded to the introductory themes about what the Observatory is. its mission, vision, lines of research and methodology; Likewise, two workshops related to violence were given of gender in charge of the teachers Danny Cifuentes and Pablo Mendoza, for this they had the participation of 19 students. This first activity culminated on June 16, 2018. (There are the presentations of the four workshops). Already for the month of June with the group of students trained, it was developed and promote a second activity with the Municipality, called Legalization of Neighborhoods, product of the existing agreement with the same. There, more than 7 neighborhoods of the Canton were addressed of Otavalo under the joint interaction between officials of the Municipality, teachers of the University of Otavalo and students attached to the observatory, generating participation in the community assemblies and producing an immediate collaboration in updating the acts or statutes to adapt to the requirements of the Municipality for its activation in the social projects. These activities were extended until August 2018. (There is the certificate of satisfaction as evidence). For September and October, the Observatory participated with its students in several activities in the academic week of the University and in events such as congresses and training workshops in Criminal Oral Litigation and COGEP so that students can address these issues. Finally, in November and December the project requires the preparation of reports of activities of the students and the realization of an essay of experience of their connection with the Company, for this each one of them prepared their report as part of the pertinence necessary between the link and the research of the University.